Amplicon-based next-generation sequencing reveals the co-existence of multiple Leishmania species in patients with visceral leishmaniasis. (February 2022) - Castillo-Castañeda, Adriana; Patiño, Luz H.; Muñoz, Marina; Ayala, Martha S.; Segura, Maryi; Bautista, Jessica; Shaban, Maryia V.; Paniz-Mondolfi, Alberto; Ramírez, Juan David
Highlights: Visceral leishmaniasis can occur due to co-infection with several Leishmania spp. Co-infection in visceral leishmaniasis changes our understanding of the disease. Several trypanosomatids can be identified per sample using this protocol. Amplicon-based next-generation sequencing is a cost-effective method in molecular epidemiological studies. ABSTRACT: Visceral leishmaniasis (VL) is a mammalian protozoal disease propagated in the Americas by female phlebotomine sandflies, mainly caused by Leishmania infantum . However, in recent years, cases of VL caused by different Leishmania species, such as L. amazonensis and L. colombiensis, have been reported in the continent. This study used an amplicon-based next-generation sequencing approach to identify VL aetiologic species using high-depth sequencing targeting a region on the Heat Shock Protein 70 gene. In this first approach, six samples from five patients diagnosed with VL were selected and analysed to identify DNA of Leishmania spp. All samples harboured DNA of L. infantum ; five samples were found to be co-infected with other Leishmania spp. or with Trypanosoma cruzi, and just one sample was mono-infected with L. infantum . This study demonstrates the usefulness of this methodology to identify trypanosomatid co-infections in clinical samples, which presents an interesting study panorama considering their biological, clinical and epidemiological implications. Graphical abstract: Image, graphical abstract